Pathways to Healthcare for Migrant Workers : How Can Health Entitlement Influence Occupational Health Trajectories ? - Jill Hanley; Sylvie Gravel; Katherine Lippel; Jah-Hon Koo (Perspectives Interdisciplinaires sur le Travail et la Santé)
The aim of this study was to analyze the temporal dimension of seasonal work and to identify determinants for the sustainable prevention of musculoskeletal disorders. An ergonomic work activity study with a gender-sensitive approach was conducted. Sixteen female seafood-processing workers were monitored for two consecutive work seasons using a range of interviews, observations (work activity, production, and organization) and document analyses. The results led to the development of methodological elements for the study of seasonal work. The results also showed that the work activity could be seriously influenced by determinants pertaining to public policies and ministerial rules. Sustainable prevention of musculoskeletal disorders must consider these determinants.